2012
DOI: 10.1167/iovs.12-9910
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Endoplasmic Reticulum Stresses Mediate Apoptosis Induced by Modified LDL in Human Retinal Müller Cells

Abstract: PURPOSE. We previously showed that extravasated, modified LDL is implicated in pericyte loss in diabetic retinopathy (DR). Here, we investigate whether modified LDL induces apoptosis in retinal Müller glial cells. METHODS. Cultured human retinal Müller cells (MIO-M1) were treated with highly oxidized glycated LDL (HOG-LDL, 200 mg protein/L) or native LDL (N-LDL, 200 mg protein/L) for up to 24 hours with or without pretreatment with N-acetyl-cysteine (NAC, a blocker of oxidative stress) and 4-phenylbutyrate (4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 54 publications
(92 reference statements)
10
53
1
Order By: Relevance
“…Intra-retinal ox-LDL was associated with apoptosis, and in proliferative DR, with macrophage infi ltration ( 8 ). Consistent with a generalized retinal injury ( 18 ), in vitromodifi ed LDL was toxic toward Müller cells and RPEs as well as toward vascular cells (9)(10)(11)(12)(13)(14)(15). In the present work, CD36 and CD64 blockade inhibited apoptosis and improved mitochondrial function ( Fig.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Intra-retinal ox-LDL was associated with apoptosis, and in proliferative DR, with macrophage infi ltration ( 8 ). Consistent with a generalized retinal injury ( 18 ), in vitromodifi ed LDL was toxic toward Müller cells and RPEs as well as toward vascular cells (9)(10)(11)(12)(13)(14)(15). In the present work, CD36 and CD64 blockade inhibited apoptosis and improved mitochondrial function ( Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with a general neurovascular retinal insult in DR ( 18 ), we also found evidence of a broad array of cytotoxic effects: "highly oxidized, glycated LDL" promoted oxidative stress, endoplasmic reticulum (ER) stress, infl ammation and abnormal gene expression, and decreased viability, not only in retinal vascular cells (endothelial cells, pericytes), but also in Müller glia and retinal pigment epithelial cells (RPEs) (9)(10)(11)(12)(13)(14)(15).…”
Section: Flow Cytometry For Cell Surface Receptorssupporting
confidence: 70%
See 2 more Smart Citations
“…Lyons' team has shown that extravasated and modified LDL and immune-complexed oxLDL are present in the retina of diabetic patients. They have also demonstrated that glycated LDL and/or oxLDL exert cytotoxicity to cultured human retinal capillary endothelial cells [192], pericytes [166,[192][193][194][195], retinal pigment epithelium [165], and Muller glial cells [196]. Finally, these glycated LDL could be shown to cause changes in cell signaling, gene expression, cell apoptosis, and autophagy [165,192,193,195,196].…”
Section: Lipid-and Lipoprotein-related Biomarkersmentioning
confidence: 99%